2018
DOI: 10.1007/s10552-018-1109-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying optimal approaches to scale up colorectal cancer screening: an overview of the centers for disease control and prevention (CDC)’s learning laboratory

Abstract: Use of recommended screening tests can reduce new colorectal cancers (CRC) and deaths, but screening uptake is suboptimal in the United States (U.S.). The Centers for Disease Control and Prevention (CDC) funded a second round of the Colorectal Cancer Control Program (CRCCP) in 2015 to increase screening rates among individuals aged 50–75 years. The 30 state, university, and tribal awardees supported by the CRCCP implement a range of multicomponent interventions targeting health systems that have low CRC screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Although the costs per cancer averted or quality-adjusted life-year gained are important outcomes, the cost per additional person screened is often the outcome of most relevance to decision makers at community health clinics. [44][45][46] Moreover, the association between improved CRC screening through organized programs and substantial reductions in CRC incidence and mortality over longer-term time horizons was previously demonstrated, 47 and multiple other studies have demonstrated the cost-benefit tradeoffs of CRC screening more generally. Our current study focused more narrowly on the most efficient strategies to increase uptake of CRC screening in low-income Medicaid enrollees, as opposed to the value of screening itself.…”
Section: Discussionmentioning
confidence: 84%
“…Although the costs per cancer averted or quality-adjusted life-year gained are important outcomes, the cost per additional person screened is often the outcome of most relevance to decision makers at community health clinics. [44][45][46] Moreover, the association between improved CRC screening through organized programs and substantial reductions in CRC incidence and mortality over longer-term time horizons was previously demonstrated, 47 and multiple other studies have demonstrated the cost-benefit tradeoffs of CRC screening more generally. Our current study focused more narrowly on the most efficient strategies to increase uptake of CRC screening in low-income Medicaid enrollees, as opposed to the value of screening itself.…”
Section: Discussionmentioning
confidence: 84%
“…The total implementation cost for all EBIs was calculated to be $40908.97, and the cost per additional screen was $144.65. Although the incremental cost is higher for this health system than for some other FQHCs that implemented multicomponent interventions (Lara et al, 2018;Tangka et al, 2019), we believe that this is in part caused by manual entry of provider and patient reminders into the EMR. As this health system moves toward a more automated system of reminders, we expect that this incremental cost will decrease.…”
Section: > > Discussionmentioning
confidence: 86%
“…West Virginia University's patient reminder interventions increased the average FIT kit return rate by 19.6 percentage points (Conn et al, 2019). The average total incremental cost per FIT kit returned across all nine FQHCs was $60.18, but incremental cost per person screened varied widely.…”
Section: Screening Uptakementioning
confidence: 99%
“…Beginning in fiscal year 2015, the emphasis of the CRCCP shifted from screening to implementation of evidence-based interventions (EBIs), and CDC funded 30 state health departments, academic medical centers and universities, and a tribal organization to help health systems implement interventions to reduce disparities in CRC screening (DeGroff et al, 2018). CDC and RTI International then partnered with a select number of awardees to conduct economic evaluations to assess the cost-effectiveness of the EBIs (Subramanian et al, 2020;Tangka et al, 2019 Cost of travel; childcare payments related to visits; copayment; loss of income due to time required to receive health services Multilevel interventions and strategies to increase CRC uptake (e.g., patient reminders, provider reminders, provider assessment and feedback, reduction of structural barriers, reduction of patient out-of-pocket cost, one-on-one education, small media)…”
mentioning
confidence: 99%